Polysemy of English “But” and Challenges in its Translation into Kurdish (Global Journal of Human-Social Science, 2023)
This study demonstrates an innovative method practice of utilizing translation to study the linguistic phenomena connectives cf Moeschler 1989 Degand 2009 Based on the Relevance Theoretic Framework and polysemy approach this paper consolidates research that examines the polysemy of English but cf Wilson and Sperber 2004 Fischer 2006 and rejects the ambiguity account by Anscombre and Ducrot 1977 and Hall 2004 and also establishes a paradigm of correspondences for but in Kurdish Data for this study consists of 50 opinion articles from English and Kurdish online newspapers All the occurrences of but and its equivalents in Kurdish are examined and translated in order to build the paradigm of correspondences The study suggests that there are four different interpretations of a general procedure encoded by but namely contrary to expectations contrast correction and dismissal and that these procedural meanings are translated into Kurdish as ke i be am be p ewanewe and be k respectively
Keywords: discourse analysis; relevance theory; connectives; translation